Undifferentiated Pleomorphic Sarcoma Presenting With Cardiac Tamponade: A Case Report and Review - Swathi Prakash MD; Jose Luis Rayas MD; Adrian Rojas Murguia MD; Ajay Lingireddy MD; Mariam Hassan MD; Sara Alhariri MD; M. Nawar Hakim MD; Fatma Dihowm MD, MS; Satish Maharaj MD (SAGE Publishing, 2022)
Soft tissue sarcomas (STS) comprise a large group of heterogeneous malignant tumors that form approximately 1% of all adult malignancies. Most sarcomas originate from soft tissue and the rest arise from the bone. Undifferentiated pleomorphic sarcoma (UPS) is an aggressive tumor that usually presents as an asymptomatic subcutaneous mass that exhibits rapid growth with unremarkable skin findings. The diagnosis is usually made with histopathology or immunohistochemistry; once the diagnosis is confirmed, evaluation and workup of the primary tumor, lymph nodes, and metastasis should be made. Treatment is stage-dependent but generally involves en-bloc resection followed by a review of pathology with a discussion of the benefits of adjuvant radiation or chemotherapy. Here, we discuss a case of a 77-year-old patient who presented with a large mass over the right shoulder and echocardiographic findings of cardiac tamponade.